Analysis of higher order thinking skills questions in reading exercises of "Bright" book for ninth grade - Parel, M.Ewaldo; Sujarwati, Iis (Journal of English Language Teaching and Learning (JETLE), 2024)
This research aims to identify the cognitive dimensions present in the textbook "Bright" and examine the composition and distribution of higher order thinking skills in reading exercises as classified by Revised Bloom's Taxonomy. The research employs a descriptive quantitative methodology, focusing on the ninth-grade textbook "Bright," published by Erlangga in 2024. Data collection was conducted using a checklist instrument. The findings reveal that: 1) The reading questions in the "Bright" textbook encompass only five cognitive dimensions: remembering, understanding, applying, analyzing, and evaluating. 2) Analysis results indicate that 92.8% of the reading questions are categorized as Lower Order Thinking Skills (LOTS), while only 7.2% fall under Higher Order Thinking Skills (HOTS). This suggests a predominance of Lower Order Thinking Skills over Higher Order Thinking Skills in the reading questions of the "Bright" textbook. Consequently, the questions presented in the "Bright" textbook primarily focus on Lower Order Thinking Skills rather than fostering Higher Order Thinking Skills. Relying solely on the English textbook as a pedagogical resource is insufficient for enhancing students' abilities in Higher Order Thinking Skills.